Effect of nitrogen and energy supplementation on intake, digestibility and rumen fermentation efficiency in sheep fed poor quality Eragrostis curvula hay - Van Niekerk, Willem A. (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.